Identification of care needs of patients with and without the use of a classification instrument - Perroca,Marcia Galan (2014)
Objective: To analyze the agreement and disagreement between the assessments by applying or not a patient classification instrument, and to investigate the association between the agreement and personal and professional characteristics of the evaluators. Method: This is a descriptive exploratory study. 105 patients were hospitalized in a teaching hospital in the state of Sao Paulo, using the kappa statistic (weighted) and the Bootstrap method. Results: The agreement between the assessments were​​: kw 0.87 (instrument x internal evaluator), kw 0.78 (instrument x external evaluator) and kw 0.76 (between evaluators) and the influence of some personal and professional characteristics. The assessments conducted through the use of an instrument contemplated a greater number of areas of care in relation to when the instrument was not applied. Conclusion: The use of this instrument is recommended in order to more effectively identify care needs of patients.